Tanulóközpontú módszerek motivációs elemzése a földrajztanulásban és tanításban - Béres, András (Kultúratudományi Szemle, 2023)
Frontal teaching is still one of the most used teaching methods in Hungary's public education. The central theme of my publication is the methodological and motivational analysis of approaches and forms of learning methods that can be applied in geography classes and used as a substitute for frontal teaching. I aimed to involve students as much as possible in teaching a particular geographic topic (hydrosphere), so I used different forms of learning in the classroom: breakout room, data analysis, mathematical tasks, debate, cooperative and collaborative work, and atlas-centred tasks. The study was conducted in two ninth-grade classes parallel to each other in a high school. My thesis consists of two parts. The first part is a methodological analysis, a summary, followed by related motivational research. The study is based on a set of questionnaires that I have modified. Most of my hypotheses were confirmed, i.e., the student’s willingness to participate in class was high, the results in the final test were good, and the factors measuring motivation to learn showed medium-high results. At the end of my research, I concluded that elevated levels of student engagement in class are more effective and bring many benefits, so various means and practices can minimise the role of frontal teaching.